Extraction Optimization of Polysaccharides From Corn Silk and Their Antioxidant Activities in vitro and in vivo - Zhang, Liang; Yang, Yang; Wang, Zhanyong (Frontiers in Pharmacology, 2021)
Response surface technique was employed for improving the extraction of corn silk polysaccharides (CSP). Temperature, liquid-to-solid ratio, and per extraction time were all examined as separate factors. The optimal extraction parameters were determined by fitting experimental data to a second-order polynomial; a liquid-to-solid ratio of 21.5 ml/g, temperature equivalent to 88°C, and extraction time of 1.87 h. The experimental yield of the extracted polysaccharides following the application of these conditions was 4.33 ± 0.08% (dry weight), which fit quite well with the predicted value. CSP’s strong scavenging capabilities against hydroxyls, 1,1-diphenyl-2-picrylhydrazyl radicals, and superoxide anions along with its excellent reducing potential, were demonstrated in an in vitro antioxidant experiment. Meanwhile, in vivo testing revealed that CSP substantially enhanced glutathione peroxidase and superoxide dismutase activities. The Malondialdehyde levels in the liver and serum of aged mice also underwent a decrease. This study found that CSP has a substantial antioxidant potential in vitro and in vivo, suggesting that it might be used as an antioxidant in food and medicine.